Evolutionary biology: annelid who's who - Arendt, Detlev (Nature, 2011)
The origin of the annelids is buried in distant evolutionary time. A molecular phylogeny resolves their deep family interrelationships and provides a picture of their 'urannelid' ancestor. See Letter p.95